ANTESEDEN LOYALITAS PELANGGAN - Belamapa, Rizky Bionie; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to analyze the effects from advertising towards brand awareness and corporate image, also services quality towards customer’s satisfaction and its influence on customer’s loyalty from Telkom phone’s customers. The variables used in this study are advertising and services quality as independent variables, then the brand awareness, corporate image, customer’s satisfaction as intervening variables and customer’s loyalty as the dependent variable. This sample in this study was 200 respondents of Telkom phone’s customers in Semarang. The method used is Accidental Sampling by distributing questionnaires to the respondents. In this study developed a theoretical model to propose seven hypotheses to be tested using analysis tools Structural Equation Modeling (SEM0 which is operated through a program AMOS 20.0 Based on research of data processing SEM for full model has met the criteria of goodness of fit as follows: the value of chi-square = 152,754; probability = 0,059; RMSEA = 0,035; CMIN/DF = 1,203; GFI = 0,902; AGFI = 0,868; TLI = 0,977; CFI = 0,981. Within the result, it can be said that this model is feasible to be used. The result showed that the customer’s loyalty can be improved by increasing services quality affect the customer’s satisfaction as a determinant of success increase customer’s loyalty.